"Jusque-là, accroche-toi, tu m'entends?" Hello happy taxpayers, numéro 7 - Ruijters, Marcel 1966-; Valium, Henriette 1959-2021; Bolino, Pakito 1966- (H.H.T., 1988)
Record reviews, interview with Jean-Louis Costes, Blast First dossier, article on Swans, interview with The Ex, interview with Culturcide, texts, the cinema of Yann Beauvais, interview with Sleep Chamber, text, interview with Sonic Youth, interview with Das Synthetische Mischgewebe, interview with Z'EV, interview with Nox, fanzine reviews, Joubert interview, RRR Records dossier, lyrics, Made in Britain review, record & cassette reviews...
Offsetdruck. - Umschlag: farbig
Keywords: Graphzine